An Evaluation of Open-Source LMS for e-Learning courses - Kumari, Prabha; Thakur, Sanjeev (International Journal of Computer Sciences and Engineering, 2015)
Due to rapid growth in the e-Learning area evolution is seen in the education sector e-Learning is the most effective mode of education by providing learner convince to access the study material anytime, anywhere according to their convenient . LMS and LCMS is the backbone of any e-learning system. Learning Management System and Learning Content Management System is software tool essential to the deployment and management of e-learning courses. In e-Learning area there are various proprietary as well as Open Source LMS exists in the market. In the past few years there are numbers of open source LMS emerged as alternative to the proprietary LMS. In this paper we concentrated on the open source LMS Moodle, Sakai, eFront and Forma LMS. This will help the administrators and educators and organisation in choosing of learning management system that is most suitable for their needs.